The Expenditure Patterns and Consumer Rationality - Joshi, Uttam Lal (International Research Journal of MMC, 2023)
Emerging issue in consumer behavior theory is consumer rationality where it has certain relationship with income and expenditure of consumers. Consumer rationality is binary dependent variable which can be expressed in three dimensions- price, quality and brand. The major objective of this study is to examine the relationship of consumer rationality with income and expenditure of the consumers. It aims to explain the impact of income and expenditure on consumer rationality. Primary data are obtained from the survey questionnaire from Hetauda sub- metropolitan city and entered into statistical software e.g. SPSS and E-Views for inferential analysis then binary logistic regression model is used for the relationship of consumer rationality with income and expenditure of the consumers. Binary logistic results show expenditure and number of family members are significant at 5 percent and 10 percent level of significance for consumer rationality on price. Income and expenditure are significant at 5 percent level and number of family members is significant at 10 percent level of significance for quality dimension. Expenditure of the consumers is significant at 5 percent level and occupation is significant at 10 percent level for brand. So consumer rationality is influenced by income and expenditure of the consumer where higher the level of income and expenditure show the higher awareness towards rationality.